Considerations for maintaining resource adequacy of electricity systems with high penetrations of PV and storage. (1st December 2020) - Cole, Wesley; Greer, Daniel; Ho, Jonathan; Margolis, Robert
Highlights: We model high PV and storage penetration scenarios of the United States. 7 years of coincident wind, solar, and load data are incorporated in the model. The most challenging periods to serve load shift to late evenings and early mornings. Non-PV and storage resources still play an important role in resource adequacy. At very high penetration snowfall might be an issue for PV in the wintertime. Abstract: Solar photovoltaic (PV) and energy storage deployment has grown rapidly in recent years and is expected to continue as the costs of these technologies continues to decline. As PV penetration grows, peak net load hours—where net load is load minus variable renewable energy generation—become increasingly important for understanding resource adequacy of power systems. In this work, we evaluate scenarios of a future U.S. power system with high penetrations of PV. We do so by using a national-scale capacity expansion model to consider 15 scenarios with national annual PV generation penetration levels of 16%–47%, combined wind and PV penetrations are 40%–64%, and storage capacity ranging from 5% to 47% of peak demand. The modeled scenarios incorporate 7-years of coincident weather data and load profiles (2007–2013) for the contiguous United States. In doing so, we evaluate when peak net load hours occur and how their occurrence is impacted by PV penetration, region, and weather. We find that with increasing PV penetration, peak net load hours move from afternoon periods to evenings or from midmorning to early morning, and that the frequency of winter peak net load hours increases. We also simulate hourly system dispatch in 3 of the 15 scenarios using a commercially available unit commitment and dispatch model—PLEXOS– to evaluate with much greater resolution how the systems behave under specific weather conditions observed from 2007 to 2013. The hourly results show substantial shifts in how peak net load hours are served as PV penetration increases, and that how the system serves those top peak net load hours varies considerably across different regions of the country. Finally, we employ a simple method for estimating the impacts of snow cover in the high PV penetration scenarios and find that for the moderate and highest levels of PV we examine, snow cover has the potential to result in capacity and energy shortfalls.